Multi-Angle Light Scattering: An Efficient Tool Revealing Molecular Structure of Synthetic Polymers - Podzimek, Štěpán (Wiley-VCH, 2019)
Multi-angle light scattering (MALS) photometers represent the most effective solution of the traditional problem of size-exclusion chromatography (SEC), which is column calibration by means of narrow polymer standards. In addition to the ability to provide true molar mass distribution independently of any polymer standards, the combined SEC-MALS technique is able to yield other important characteristics of polymers such as chain conformation and branching. Coupling an SEC-MALS set-up with an online viscosity detector is another step forward to the detailed insight into the polymer molecular structure. Asymmetric flow filed flow fractionation (AF4) is an alternative analytical separation technique capable of replacing SEC in the case of its failure. The paper provides a brief overview of various applications of SEC-MALS and AF4-MALS in the R&D and quality control of industrial polymers including introduction into basic theoretical principles.
Víceúhlový rozptyl světla: Účinný nástroj pro objasnění molekulární struktury syntetických polymerů
Keywords: branched polymer; gel permeation chromatography (GPC); light scattering; molecular weight distribution molar mass distribution; separation techniques; víceúhlový rozptyl světla; frakcionace tokem v asymetrickém tokovém poli; inline viskozimetrie